2016
DOI: 10.1080/21645515.2016.1165373
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a single dose 23-valent pneumococcal polysaccharide vaccine in Russian subjects

Abstract: PPV23 is generally safe, well tolerated, and highly immunogenic when given as a single dose to Russian individuals 50 y of age and older, as well as Russian individuals 2 to 49 y of age who are at high risk for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…For persons ≥ 2 years of age, numerous studies have shown that PPV23 is effective in preventing IPD. Recent studies from Russia, 21 China 22 and Japan 23 demonstrated that geometric mean antibody titers (GMTs) to all tested serotypes increased dramatically after PPV23 vaccination. High proportions of subjects had ≥2-fold increases in IgG antibodies; for example, rates for serotypes 1, 6B, 14, 19F, and 23F were 92%, 83%, 89%, 81%, 84%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For persons ≥ 2 years of age, numerous studies have shown that PPV23 is effective in preventing IPD. Recent studies from Russia, 21 China 22 and Japan 23 demonstrated that geometric mean antibody titers (GMTs) to all tested serotypes increased dramatically after PPV23 vaccination. High proportions of subjects had ≥2-fold increases in IgG antibodies; for example, rates for serotypes 1, 6B, 14, 19F, and 23F were 92%, 83%, 89%, 81%, 84%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…High proportions of subjects had ≥2-fold increases in IgG antibodies; for example, rates for serotypes 1, 6B, 14, 19F, and 23F were 92%, 83%, 89%, 81%, 84%, respectively. 21 Opsonophagocytic assay (OPA) GMTs also increased significantly, ranging from 8.2 to 65.4 23 . (See Table 2 for recent clinical trials concerning PPV23 vaccination in healthy populations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of pneumococcal vaccinations against pneumonia is widespread (7478). Furthermore, due to its long practice in the clinic, many optimizations of the vaccine have taken place, guaranteeing its safety even in vulnerable individuals such as pregnant women, young children, and the elderly (7577). It should be noted that different S. pneumoniae strains as well as other bacteria, possess the phosphorylcholine epitope that triggers the production of anti-oxLDL IgM autoantibodies by means of molecular mimicry (31, 79).…”
Section: Discussionmentioning
confidence: 99%
“…The use of pneumococcal vaccinations against pneumonia is widespread (74-78). Furthermore, due to its long practice in the clinic, many optimizations of the vaccine have taken place, guaranteeing its safety even in vulnerable individuals such as pregnant women, young children and the elderly (75)(76)(77). It should be noted that different S. pneumoniae strains, as well as other bacteria, possess the phosphorylcholine epitope that triggers the production of anti-oxLDL IgM autoantibodies by means of molecular mimicry (31,79).…”
Section: Pneumococcal Immunization Reduces Neurological and Hepatic Symptoms In A Mouse Model Formentioning
confidence: 99%